The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12640-017-9814-x
|View full text |Cite
|
Sign up to set email alerts
|

L-Serine: a Naturally-Occurring Amino Acid with Therapeutic Potential

Abstract: In human neuroblastoma cell cultures, non-human primates and human beings, L-serine is neuroprotective, acting through a variety of biochemical and molecular mechanisms. Although L-serine is generally classified as a non-essential amino acid, it is probably more appropriate to term it as a "conditional non-essential amino acid" since, under certain circumstances, vertebrates cannot synthesize it in sufficient quantities to meet necessary cellular demands. L-serine is biosynthesized in the mammalian central ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 80 publications
0
48
0
Order By: Relevance
“…Research examining the impacts of dietary serine supplementation on humans and rodents showed no adverse effects [4]. Our recent studies with mice showed that serine, as a precursor of glutathione, could alleviate hepatic oxidative stress by regulating the expression of glutathionesynthesis-related genes and increasing glutathione concentration [6,7].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Research examining the impacts of dietary serine supplementation on humans and rodents showed no adverse effects [4]. Our recent studies with mice showed that serine, as a precursor of glutathione, could alleviate hepatic oxidative stress by regulating the expression of glutathionesynthesis-related genes and increasing glutathione concentration [6,7].…”
Section: Introductionmentioning
confidence: 96%
“…Serine, recently classified as a conditionally non-essential amino acid, has been suggested as playing important roles ranging from protein synthesis to cell signal transduction, the latter mostly through post-translational modification by phosphorylation [4,5]. Research examining the impacts of dietary serine supplementation on humans and rodents showed no adverse effects [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, l -serine exerts critical functions in the mammalian central nervous system. It serves as a precursor of the neuroactive substances l -serine and glycine, and mediates neuroprotective effects ( 25 , 26 ). However, it remains unknown whether l -serine has any effects on age-related oxidative stress in the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for non-primary protein association in favor of misincorporation also exists [ 34 ]. Furthermore, despite reports that BMAA does not misincorporate into proteins in bacteria or in a rat pheochromocytoma cell line [ 34 , 69 ] it has been suggested that the lack of prokaryote misincorporation may not hold true in eukaryotes [ 75 ], although the authors cite Glover et al [ 32 ] in support of their hypothesis, despite their use of a prokaryotic expression system. In this study, human cell lines were therefore used to evaluate BMAA misincorporation using both toxicological markers and amino acid compositional analysis of purified proteins from exposed cell lines, with reference to known misincorporating amino acid analogues.…”
Section: Introductionmentioning
confidence: 99%